The impact of an indigenous proverb on women's mental health: A phenomenological approach - Seepaneng S. Phiri; Fhumulani M. Mulaudzi; Tanya Heyns (AOSIS, 2015)
Background: Proverbs and idioms represent cultural and societal beliefs and values inherited from the forefathers. An example is lebitla la mosadi ke bogadi. Over many decades African people have used such ancient instructions to counsel women to be resilient in their marriages thus impacting on their mental health. Objective: The purpose of this article was to explore and describe that proverb and its impact on women's mental health. Method: Hermeneutic phenomenology was used to explore and describe the prover band its impact on indigenous women's mental health. The population included married, divorced, widowed and single women who were attending social clubs or networks in the cities of Tshwane and Johannesburg. Snowball and purposive sampling was used to select 57 participants. Five face-to-face interviews and eight focus groups interviews were conducted. Colaizzi's data analysis method was used to analyse data. Results: Oppression and stigmatisation of women and their families and harmful effects that may result in death were identified as having an impact on women's mental health. Some women shared that they were oppressed in many ways. In addition, they feared stigmatisation should they wish to divorce. They constantly lived in fear of being harmed or killed by their spouses. Conclusion: There was a need for nurses to develop awareness regarding cultural issues so that women are better served in primary healthcare settings. Women who are suspected of experiencing abuse, should be screened for abuse so that they can be assisted accordingly.